The Development of PISA Type Evaluation Instruments with Ethnothematic Characteristics of Kudus Local Islamic Culture - Mulyani Putri Wulandari; Arghob Khofya Haqiqi (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2022)
This study aims to determine the development and feasibility of the PISA type evaluation instrument with the ethnomathematical characteristics of the local Islamic culture of Kudus. This evaluation instrument is more appropriate if used at the time of learning evaluation. By using this evaluation instrument, students do not only study mathematics, but also about Islamic culture in Kudus. The type of research used is Research and Development with the ADDIE model. The results of this study are in the form of an evaluation instrument product of the PISA type with the ethnomathematical characteristics of the local Islamic culture of Kudus in class VII mathematics is sets, lines and angles, rectangles and triangles, and the results of the product feasibility test obtain the same CVR value of 1, because all validators assigns an essential value (E) to each instrument. So that the results obtained state that the instrument is valid, and the conclusion states that the instrument is suitable for use without revision. After being declared feasible without revision, then a small and large trial was carried out using 4 feasibility tests, namely validity test, reliability test, difficulty level test, and discriminatory power test. With the results of the calculation of small and large trials using validity and reliability tests, the results are both valid and reliable. So that it can be categorized as feasible and can be used in the evaluation of class VII mathematics learning.